Emerging athletes` career transitions in professional sport: an existential multi-case perspective - Thomas, P. G.; Lucas, P.; Walters, S.; Oldham, A. R. H. (Frontiers in Sports and Active Living, 2024)
Introduction: This article examines athletes preparing for, transitioning into, or going through the developmental stages of a professional sports career, referred to as the emerging athlete career transition. This transition includes events such as selections, Junior-to-Senior promotions, contracting, migration, and early exits. The article presents the collective findings of a multi-case study in three professional sports: rugby league, basketball, and boxing.